2022
DOI: 10.3389/fendo.2022.889029
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polycystic Ovary Syndrome Phenotypes With Adverse Pregnancy Outcomes After In-Vitro Fertilization/Intracytoplasmic Sperm Injection

Abstract: ObjectiveThis study aims to evaluate the association between polycystic ovary syndrome (PCOS) phenotypes and adverse perinatal outcomes, comparing the characteristics, ovarian response, and assisted reproductive outcomes in patients with various PCOS phenotypes after in-vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI).MethodsThis study comprised 6,732 patients who underwent the first cycle of IVF/ICSI treatment in our outpatient department from January 2017 to July 2018. Propensity score match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…Age was comparable in the different phenotypes. These results were close to whom the total doses were comparable in the different phenotypes [3].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Age was comparable in the different phenotypes. These results were close to whom the total doses were comparable in the different phenotypes [3].…”
Section: Discussionsupporting
confidence: 84%
“…We thus distinguish four phenotypes. PCOS is the major cause of anovulatory infertility [3] [4] [5] [6]; In Vitro Fertilization (IVF) constitutes the final stage of care for this group of patients and according to several authors, the outcome in IVF/ICSI (In Vitro Fertilization/Intracytoplasmic Sperm Injection) would depend on the PCOS phenotype [3] [6] [7] [8]. Thus, given the recurrence of cases of PCOS admitted for ovarian stimulation for IVF/ICSI at the Hospital Center for Research and Application in Endoscopic Surgery and Human Reproduction (CHRACERH) and the fact that no study on this subject has been carried out in our context which we proposed to carry out this study.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study by Wang et al indicated that the PCOS phenotype was correlated with adverse pregnancy outcomes (ectopic pregnancy, miscarriage, and premature birth), and PCOS phenotypes A and D were the independent risk factors for adverse pregnancy outcomes. However, CPR and LBR in various PCOS phenotypes were comparable in that study [18], even with a significantly larger population group. Few studies have tried correlating the PCOS Phenotype with oocyte morphology and ICSI outcome [19,20], although the connection has been conflicting [21].…”
Section: Discussionmentioning
confidence: 48%
“…De Vos et al demonstrated that phenotype D had a higher live birth rate and cumulative clinical pregnancy rate compared to phenotypes A and C, after excluding the influence of phenotype B [49]. When compared to those without PCOS, the incidence of adverse pregnancy outcomes, such as ectopic pregnancy, miscarriage, preterm birth, and hypertensive disorders, was found to be higher in women with PCOS exhibiting phenotypes A and D [50]. HA phenotype PCOS is associated with increased rates of spontaneous abortion and pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%